Information System Design Web-Based Cash Bookkeeping Case Study of Juice Shop 1 Putra - Nadaa, Namira Kaltsum (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
The development of increasingly advanced technology makes business actors have to follow the developments that occur in the entrepreneurial environment. In this study, he designed a website-based cash bookkeeping at Toko Jus 1 Putra. In-store cash bookkeeping is still done manually, so the creation of reports is quite time-consuming and what is produced cannot be optimally. The purpose of this study was to produce easy and accurate cash bookkeeping in recording reports during sales transactions, the purchase of Jus 1 Putra. The research method used is Waterfall and uses the Laravel framework. The testing method used is Black Box Testing. In data collection carried out through observation, interviews, and literature studies. The results of this research that have been built by the infrastructure system are successful, based on the design of business needs provide with features that help to carry out business processes.